Analysis of the Relationship Between E-Learning Service Quality and Student Trust, Student Satisfaction, and Student Loyalty - Dodi Ria Atmaja; Heldina Marta br Sagala (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
The research was conducted to explore the impact of service quality on student loyalty with student satisfaction and student trust as mediation.Â This sorting is expected to contribute to the university in adding information and positive managerial implications to its management. This research aims to demonstrate that the quality of services on e-learning in affecting several other factors is also able to increase student loyalty. The research population was 95 respondents active students at Esa Unggul University. The questionnaire data collection took place online in February 2023. The method used for data analysis is partial least squares structural equation structure equation modeling. The results show that there is a positive impact of service quality, student satisfaction, and student trust. There is also a role of student satisfaction mediation, and student trust. The research is expected to contribute to educational institutions in improving the quality role of e-learning services aimed at increasing student loyalty to universities.